Food systems for human and planetary health: Economic perspectives and challenges - Fan, Shenggen; Headey, Derek D.; Rue, Christopher; Thomas, Timothy S. (Annual Reviews, 2021)
Food systems are currently facing unprecedented challenges. More than 690 million people still suffer hunger while climate change, rapid depletion of natural resources, and loss of biodiversity further threaten future food systems. Influential global reports emphasize the need for fundamental transformations of food systems for human and planetary health, but few incorporate economic considerations. This review adopts an economic lens to assessing potential transitions to ideal food systems that are productive, sustainable, nutritious, resilient, and inclusive. Our findings show that new technologies, policies, institutions, and behavior changes can leverage synergies for achieving multiple food system targets, but rigorous economic analysis is needed to further analyze trade-offs and to overcome complex behavioral, institutional, and political barriers. This review also points to important knowledge gaps that economists and other social scientists must address to contribute to the radical transformation of food systems.